Penerapan Metode Simple Additive Weighting dan Pembobotan Entropy Untuk Penentuan Teknisi Terbaik - Aditia Yudhistira (Journal of Artificial Intelligence and Technology Information (JAITI), 2024)
Determining the best technicians in a company is often a challenge due to a variety of factors that need to be considered. Each technician has different advantages and disadvantages, making objective performance measurement difficult. This problem is often exacerbated by the subjectivity of assessments, especially if the evaluation is based solely on the subjective assessment of the supervisor or management team without considering in-depth performance data. The application of the SAW method with entropy weighting for the determination of the best technician is an approach that combines a simple calculation process with objective criterion weighting, based on the degree of variability of data between technicians. The combined application of SAW and entropy provides a fair, objective, assessment system in determining the best technicians, which is able to help companies to identify the technicians with the most superior performance. The results of the analysis of the selection of the best technician using the SAW method show that Technician E is ranked at the top with a final score of 0.8619, making it the best choice based on the criteria that have been assessed. The next ranking was filled by Technician A with a score of 0.8381, and Technician C who obtained a score of 0.8310, showing their excellent performance.